Assessing current functioning as a measure of significant reduction in activity level. Issue 3 (2nd July 2016) - Thorpe, Taylor; McManimen, Stephanie; Gleason, Kristen; Stoothoff, Jamie; Newton, Julia L.; Strand, Elin Bolle; Jason, Leonard A.
ABSTRACT: Background : Myalgic encephalomyelitis and chronic fatigue syndrome have case definitions with varying criteria, but almost all criteria require an individual to have a substantial reduction in activity level. Unfortunately, a consensus has not been reached regarding what constitutes substantial reductions. One measure that has been used to measure substantial reduction is the Medical Outcomes Study Short-Form-36 Health Survey (SF-36). [1 ] Purpose : The current study examined the relationship between the SF-36, a measure of current functioning, and a self-report measure of the percent reduction in hours spent on activities. Results : Findings indicated that select subscales of the SF-36 accurately measure significant reductions in functioning. Further, this measure significantly differentiates patients from controls. Conclusion : Determining what constitutes a significant reduction in activity is difficult because it is subjective to the individual. However, certain subscales of the SF-36 could provide a uniform way to accurately measure and define substantial reductions in functioning.